Bible translation in Africa. What implications does the new UBS perspective have for Africa? An overview in the light of the emerging new UBS translation initiative - A. O. Mojola (Acta Theologica)
This article gives a brief overview of the present Bible translation situation in Africa in global and historical perspective. Special focus is given to the shifts that have occurred with respect to its vision and mission and its ever widening outreach in pursuit of the Christian great commission. Shifts in the nature and types of Bible translators at different periods are looked at as well as the question of the source and receptor texts involved in the translation. The question of the various approaches to translation that have been influential receives attention with special attention being given to the dynamic- and functional-equivalent approach popularised by Eugene Nida. The rest of the paper dwells on the way forward for Bible translation in Africa in view of the influence of the past and in view of the influence of the new approaches and insights from the emerging academic field of translation studies. The recent shift in the UBS approach to translation is briefly and broadly looked at and its implication for Bible translation in Africa discussed.